Nutritional value and Energy Balance of Pearl Millet Fodder as Influenced by Different Nutrient Management Practices - Rakesh Kumar; Hardev Ram; Rakesh Kumar; R.K. Meena; Sandeep Kumar; V.K. Meena (Indian Journal of Dairy Science, 2023)
Fodder deficiency and its poor-quality leads to lower productivity of Indian cattle. To improve productivity and nutritional value of fodder pearl millet, the present study was undertaken during kharif season of 2019-20 at Agronomy research farm, ICAR-NDRI, Karnal, and laid out in Randomized Block Design with eight treatments, viz. T1: Absolute control; T2: 100% RDF; T3: 100% RDF + Cow urine foliar spray (CU); T4: 100% RDF + PGPR; T5: 100% RDF + PGPR + Cow urine foliar spray (CU); T6: 75% RDF + Cow urine foliar spray (CU); T7: 75% RDF + PGPR and T8: 75% RDF + PGPR + Cow urine foliar spray (CU) with three replications. The results showed that the fodder nutritional value and digestibility viz., total digestible nutrients, digestible dry matter, digestible crude protein and dry matter intake increase by 28.46, 13.10, 40.26 and 8.45% respectively, with T5 treatment than absolute control. The higher energy fraction such as digestible energy (11.54 MJ/Kg), metabolisable energy (9.47 MJ/Kg), digestible feed energy (9.27 MJ/Kg), net energy (3.07 MJ/Kg) and net energy for lactation (5.29 MJ/Kg) was observed with the application of 100% RDF+PGPR+CU (T5), which was found statistically at par with applications of 100% RDF+PGPR and both were found significantly higher over rest of the treatments. Which, will further strengthen and sustain the performance of livestock in terms of health and milk production.